2007
DOI: 10.1164/rccm.200611-1739oc
|View full text |Cite
|
Sign up to set email alerts
|

Linking Parenchymal Disease Progression to Changes in Lung Mechanical Function by Percolation

Abstract: Rationale: The mechanical dysfunction accompanying parenchymal diseases such as pulmonary fibrosis and emphysema may follow a different course from the progression of the underlying microscopic pathophysiology itself, particularly in the early stages. It is tempting to speculate that this may reflect the geographical nature of lung pathology. However, merely ascribing mechanical dysfunction of the parenchyma to the vagaries of lesional organization is unhelpful without some understanding of how the two are lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 31 publications
5
102
1
1
Order By: Relevance
“…Nevertheless, merely ascribing mechanical dysfunction of the parenchyma to the vagaries of lesional organization is unhelpful without an understanding of how the two are linked. Our above results show that such a link can be forged through the concept of percolation [12], which has been invoked previously to account for numerous natural processes involving transmission of events across networks [26,27,30,31]. These simulations suggest that tissue undergoes a sharp change in its macroscopic mechanical properties at the percolation threshold, which may correspond to the point in the disease course when patients experience a sudden downturn in clinical symptoms.…”
Section: Linking Microscopic Alterations To Lung Function Via Percolasupporting
confidence: 59%
See 4 more Smart Citations
“…Nevertheless, merely ascribing mechanical dysfunction of the parenchyma to the vagaries of lesional organization is unhelpful without an understanding of how the two are linked. Our above results show that such a link can be forged through the concept of percolation [12], which has been invoked previously to account for numerous natural processes involving transmission of events across networks [26,27,30,31]. These simulations suggest that tissue undergoes a sharp change in its macroscopic mechanical properties at the percolation threshold, which may correspond to the point in the disease course when patients experience a sudden downturn in clinical symptoms.…”
Section: Linking Microscopic Alterations To Lung Function Via Percolasupporting
confidence: 59%
“…Extending this approach to large networks, we have recently shown that a sudden change in macroscopic tissue stiffness occurs when the isolated lesions become numerous enough to connect in a contiguous pathway across a large expanse of tissue [12]. This is an emergent phenomenon known to occur at the so called percolation threshold [26], and may explain why the time-course of degradation in lung function does not always mirror the progression of underlying pathology in diseases of the lung parenchyma.…”
Section: Models Of Lung Elasticty and Diseasesmentioning
confidence: 99%
See 3 more Smart Citations